Territorialités dans le Haut Rio Negro : Quelques notes sur les traductions (et les dissonances) dans la démarcation et la gestion des Terres autochtones - Iubel, Aline (Anthropologica, 2025)
The article explores the multilingual and multiethnic complexities of the Upper Rio Negro, a regional region of the Amazon region, with a focus on how different indigenous communities interact with the state and public policies regarding the demarcation of new lands. The author takes up some of Lévi-Strauss’s ideas on mythology and history to reflect on the process of land demarcation and some of its implications after about 25 years. Through examples of intercultural translations made by indigenous leaders, the article shows how indigenous people reinterpret concepts of the state to adapt them to their lived realities, revealing a dynamic process of cultural negotiation. Ultimately, the author thinks about some relationships between mythology and history, attributing new meanings to the concepts of land, territoriality and indigenous governance in a contemporary context, or to mythical narratives and political discourses continuing to dialogue.